Kritiese evaluering van die onderrig van evolusie as evolusionisme vanuit die KABV vir Lewenswetenskappe: 'n Christelike perspektief vanuit die Wysbegeerte van die Kosmonomiese Idee - Botha, Rihana; Diedericks, Morné (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2025)
This research examines the increasing emphasis on teaching evolution, particularly macroevolution, in traditional Protestant universities and the South African school curriculum. The study highlights that evolution, as outlined in the Curriculum and Assessment Policy Statement (CAPS): Life Sciences, is often presented uncritically as a worldview, effectively promoting evolutionism. This approach conflicts with the Christian worldview, creating challenges for Christian educators who wish to teach this subject. The researchers employed qualitative reflexive thematic analysis to evaluate how evolution is taught. Findings indicate that the CAPS: Life Sciences curriculum does not clearly differentiate between the scientific theory of microevolution and the more speculative aspects of macroevolution. For instance, examples such as antibiotic resistance in bacteria and variations in the beak size of Galápagos finches, which illustrate microevolution, are frequently used to support the broader concept of evolution, often presented as evolutionism. The study also reveals that tree thinking, a fundamental concept for understanding macroevolution, is inadequately addressed in the current curriculum, further contributing to misconceptions. Additionally, human evolution, a core topic in the CAPS: Life Sciences, is presented based on questionable evidence, exacerbating concerns about the uncritical teaching of evolutionism. The uncritical portrayal of evolutionism as factual truth, particularly in teaching human evolution, fosters religious tension among Christian teachers and learners. The study underscores the need to clearly distinguish between the scientific theory of evolution and the philosophical or religious perspective of evolutionism. A critical, balanced approach to teaching evolution is recommended, one that incorporates both scientific evidence and consideration of religious beliefs. Such an approach would uphold academic integrity while fostering a more inclusive and harmonious educational environment.